Caffeine as an environmental indicator for assessing urban aquatic ecosystems Cafeína como indicador ambiental prospectivo para avaliar ecossistemas aquáticos urbanos - Aldo Pacheco Ferreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
This study aimed to evaluate the co-occurrence of caffeine and the extent of its influence as compared to other traditional water quality parameters (microbiological and physico-chemical) in order to characterize it as an efficient indicator of anthropic pollution of urban aquatic environments. Caffeine is an ingredient in a variety of beverages (coffee, tea, and caffeinated soft drinks) and numerous food products (chocolate, pastries, and dairy desserts). Although the human body metabolizes this stimulant efficiently, between 0.5 and 10.0% is excreted, mostly in the urine. Analysis of water samples from the Leopoldina Basin and Guanabara Bay revealed a significant difference between areas not commonly affected by nutrient enrichment or sewage inputs and areas chronically influenced by sewage discharges and elevated eutrophication. Monitoring caffeine will be fundamental in stressed urban aquatic environments where frequent accidental ruptures of sewer lines and discharges of untreated effluents impede effective water quality evaluation with traditional indicators. Este estudo visou avaliar a co-ocorrência de cafeína e a extensão de sua influência frente a outros parâmetros tradicionais de qualidade de água (microbiológicos e físico-químicos), de modo a caracterizá-la como um eficiente indicador de poluição de origem antrópica em ambientes aquáticos urbanos. Cafeína é um componente de uma variedade de bebidas (café, chá e bebidas cafeinadas) e de numerosos produtos alimentícios (chocolate, massas e sobremesas). Embora o corpo humano seja eficiente na metabolização deste estimulante, entre 0,5-10,0% são excretados, principalmente na urina. A análise de amostras da Bacia Hidrográfica da Leopoldina e Baía de Guanabara, Rio de Janeiro, Brasil, revelou uma significante diferença entre áreas não comumente afetadas por enriquecimento de nutrientes ou esgoto, contra áreas cronicamente influenciadas por descargas de esgoto e eutrofização elevada. O monitoramento de cafeína será fundamental em ambientes aquáticos urbanos estressados, onde freqüentes rupturas acidentais de linhas de esgoto e descargas de efluentes não-tratados impedem a efetividade de avaliação da qualidade hídrica com os indicadores recomendados.